The AI factor - Saxena, Asha (Ascent Audio, 2023)
Have you heard about artificial intelligence (AI) and big data but felt they are technologies too big or too complicated for you or your business? Do you imagine AI as a Hollywood science fiction stereotype or something in the far and distant future? Take heart. AI is none of those things. It's part of our everyday lives, and it has the power to transform your business. This book will put AI, big data, the cloud, robotics, and smart devices in context. It will reveal how these technologies can dramatically multiply any businesses-including yours-by strategically using your data's latent, transformative potential. Noted business leader, data consultant, and Columbia professor Asha Saxena has distilled her twenty-seven years of experience teaching Fortune 500 leaders in this powerful and insightful book. In The AI Factor, business leaders will learn how to understand the data they already have and how to use it innovatively to grow their businesses using Saxena's unique methodology.